OPTIMALISASI SISTEM KENDALI HEXACOPTER - Al, Al; Usmanto, Febri; Premadi, Aswir; Effendi, Asnal; Bachtiar, Antonov (Jurnal Teknologi dan Vokasi, 2025)
This study aims to develop and analyze the performance of a hexacopter control system used in weather modification technology missions. Several control methods are applied, including PID, Fuzzy Mamdani, Fuzzy Sugeno, and Model Reference Adaptive Control (MRAC). The tests are conducted through simulations in MATLAB Simulink and Mission Planner, using step response parameters such as delay time, rise time, peak time, settling time, overshoot, and steady-state error as performance benchmarks. The results indicate that MRAC provides the most balanced performance in terms of speed and accuracy, Fuzzy Sugeno excels in response speed, while PID and Fuzzy Mamdani offer high stability.